Production of Light Naphtha by Flash Distillation of Crude Oil - ManuelNgoma; Chivanga BarrosAntonio André (Cognitive Sustainability, 2023)
The escalating global demand for sustainable, renewable energy sources has catalyzed research into advanced refining processes, particularly focusing on the generation of essential raw materials like light naphtha. This paper delves into the production of light naphtha via the flash distillation of crude oil, underlining its critical role in fulfilling the petrochemical industry’s requirements. The research delineates the fundamentals of flash distillation, incorporating both physical and mathematical models, with a specific emphasis on Raoult’s Law, to demystify the hydrocarbon separation process in crude oil. The mathematical framework encompasses material and energy balances, coupled with the application of liquid-vapor equilibrium equations, thereby shedding light on the thermodynamic principles steering this procedure. The progression of this study involved analyzing the distillation curve of the referenced crude oil and identifying the pseudo-components representative of the involved hydrocarbons. Utilizing the DWSIM commercial simulator, the flash distillation process of Nemba crude oil was simulated, taking into account diverse operational conditions and thermodynamic models. The outcomes were juxtaposed with industrial datasets, demonstrating a significant alignment and affirming the simulation’s predictive efficacy. A parametric sensitivity analysis was conducted to refine light naphtha yield, elucidating the effect of variables like the temperature of crude oil feed and naphtha separator feed on the process efficiency. The response surface methodology underscored the feasibility of augmenting naphtha production under certain conditions. Furthermore, this study assessed the impacts of employing two distinct thermodynamic models – the Soave-Redlich-Kwong (SRK) and Peng-Robinson (PR) equations of state. This analysis revealed minimal discrepancies in physical parameters, confirming the simulation’s robustness and the reliability of both models. The findings of this paper validate the efficacy of flash distillation in light naphtha production, with numerical simulation emerging as a potent tool for enhancing process optimization and predictive analysis. These insights not only contribute to a deeper understanding of environmental sustainability but also offer strategies for maximizing light naphtha production in the oil industry. In conclusion, the results from this investigation significantly advance our comprehension of phase equilibrium profiles and their relationship with the applied thermodynamic state equations, thereby enriching the quality of the results.